A tool-centric framework for teaching undergraduate computer science students on operating system design / Sulastri Putit and Lenny Yusrina Bujang Khedif - Putit, Sulastri; Bujang Khedif, Lenny Yusrina (UiTM Press, 2025)
Teaching and learning operating system (OS) design is a core part of computer science education, which is highly demanding for both teaching and learning. This paper presents a tool-centric framework that aims at enhancing teaching operating system design for undergraduate students in computer science. The framework integrates multiple educational tools and methodologies with the aim of making the course more appealing for students while improving their comprehension and hands-on experience in OS design. The proposed framework extends existing educational theories and practices by focusing on aspects such as computational thinking, collaborative learning, and gamification in the learning process. The theoretical basics of this framework, the practical use of such a framework, and the expected influence on students’ learning outcome will be further explained in this paper. Empirical evidence, detailed examples and comparisons with existing frameworks underscore its potential impact on student learning outcomes.